Identification of Plant Growth Promoting Rhizobacteria (PGPR) Isolated from Lavender (Lavandula angustifolia L.) and Determination of Their Antifungal Activity against Fusarium oxysporum - Murat GÜLER (ISPEC Journal of Agricultural Sciences)
Plant growth promoting rhizobacteria (PGPR) have a variety of beneficial activities, including improved nutrient absorption, phytohormone regulation, and biological control of phytopathogens. Sixteen isolates from the Lavandula angustifolia L. rhizosphere were screened for their morphological, biochemical, and plant growth promoting properties in this study. Isolates were identified using the MALDI-TOF MS method. Additionally, its antagonistic properties against the phytopathogen Fusarium oxysporum were evaluated. Among all isolates, 10 isolates (QLN-1, QLN-2, QLN-5, QLN-6, QLN-7, QLN-8, QLN-11, QLN-13, QLN-14, QLN-15) fixed nitrogen, 11 isolates (QLN-2, QLN-4, QLN-5, QLN-6, QLN-7, QLN-8, QLN-12, QLN-13, QLN-14, QLN-15, QLN-16) dissolved inorganic phosphate, 8 isolates (QLN-1, QLN-2, QLN-6, QLN-7, QLN-9, QLN-12, QLN-14, QLN-16) produced siderophore, 9 isolates (QLN-2, QLN-3, QLN-4, QLN-6, QLN -7, QLN-8, QLN-12, QLN-15, QLN-16) produced IAA and 6 isolates (QLN-5, QLN-8, QLN-9, QLN-14, QLN-15, QLN-16) produced HCN. Isolate QLN-4 showed the highest antifungal activity against Fusarium oxysporum with an inhibition rate of 57.14 %. Isolate QLN-8 isolate (24.76 %) showed the weakest effect against F. oxysporum. Although research on PGPRs has increased recently, research on lavender is still limited. Our study reveals that local bacterial isolates obtained from lavender rhizosphere can be used as microbial fertilizers and biocontrol agents.